2013
DOI: 10.1111/jvim.12073
|View full text |Cite
|
Sign up to set email alerts
|

Systemic, Renal, and Colonic Effects of Intravenous and Enteral Rehydration in Horses

Abstract: Background: Intravenous (IV) and intragastric (IG) administration of fluid therapy are commonly used in equine practice, but there are limited data on the systemic, renal, and enteric effects.Hypothesis: IV fluid administration will increase intestinal and fecal hydration in a rate-dependent manner after hypertonic dehydration, but will be associated with significant urinary water and electrolyte loss. Equivalent volumes of IG plain water will result in comparatively greater intestinal hydration with less rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 39 publications
5
58
0
1
Order By: Relevance
“…Studies conducted by Lopes et al [14], Avanza [11], Silveira et al [8] and Lester et al [17], in horses, and Atoji [15], Ribeiro Filho et al [16] in ruminants, observed this same behavior. Table 3 shows that there was an increase in the frequency of intestinal movements in animals treated with SEDext and SEMalt at T6h and T12h, whereas that increase in animals of the SEProp group was only detected at T12h.…”
Section: Discussionsupporting
confidence: 74%
“…Studies conducted by Lopes et al [14], Avanza [11], Silveira et al [8] and Lester et al [17], in horses, and Atoji [15], Ribeiro Filho et al [16] in ruminants, observed this same behavior. Table 3 shows that there was an increase in the frequency of intestinal movements in animals treated with SEDext and SEMalt at T6h and T12h, whereas that increase in animals of the SEProp group was only detected at T12h.…”
Section: Discussionsupporting
confidence: 74%
“…Recent evidence has demonstrated the efficacy of oral fluids for rehydrating ingesta and resolving impactions [16,26]. NSAIDs and oral fluids were used most frequently; spasmolytics and sedatives were also used commonly, whilst laxatives, IV fluids, opioids and electrolytes were seldom used on the primary assessment.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Lester et al . ). In these studies each horse acted as its own control, treatment were standardised and order administered randomised, therefore the quality of evidence is higher.…”
Section: Searchmentioning
confidence: 97%
“…; Lester et al . ) baseline levels of faecal hydration prior to interventions being performed are used to determine outcome. See Table .…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation